Sistem Pendukung Keputusan Pemilihan Guru Terbaik Menggunakan Kombinasi Metode Pembobotan CRITIC dan COPRAS - Sugianto, Rudi; Sulistiani, Heni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Teachers play a crucial role in shaping the future of the younger generation. They not only impart knowledge and skills, but also guide, inspire, and support students in the learning process and personal development. Selecting the best teachers involves a thorough assessment of the prospective teachers' academic qualifications, teaching experience, and communication skills. The main problem in selecting the best teachers often involves several significant challenges, namely the evaluation of teachers' skills and performance is often influenced by subjective assessments, which can result in uncertainty and bias in the selection process. The combination of the CRITIC and COPRAS weighting methods offers a robust and comprehensive approach to multi-criteria decision-making. This combination overall improves the reliability of decisions by providing a structured and comprehensive method, thus aiding in making more informative and rational choices. The results of the ranking of the best teacher, Dra. Sudarningsih received the highest score of 100, making him the best teacher in this ranking. In second place, Sri Astuti, S.Pd scored 96.64, followed by Drs. M. Jusriadi with a score of 95.54 in third place. Rita Ratna Sari, SP ranked fourth with a score of 95.45, while Misriyati, S.Pd was in fifth place with a score of 94.74. This ranking reflects an objective assessment based on the criteria that have been set, where Dr. Sudarningsih shows the best performance among the teachers evaluated.